Cis leoi, a new species of Ciidae (Coleoptera: Tenebrionoidea) from the Neotropical Region - Lopes-Andrade, Cristiano; Gumier-Costa, Fabiano; Zacaro, Adilson Ariza (Zootaxa, 2003)
Cis leoi, a new species of ciid beetle from the state of Minas Gerais, Brazil, is described based on external morphology and cytogenetics. Its placement in the Cis species group is discussed.